The role of nano fertilizers and compost in improving agricultural soil properties and their impact on faba bean productivity - Kamel Walaa M. (BIO Web of Conferences)
The research aimed to assess the effects of NPK nano-fertilizers and compost, with or without NPK mineral fertilizers, on soil properties and the productivity of local beans. The results showed that when nano-fertilizers and compost were applied, there were increases in plant height (cm), number of branches per plant, number of pods per plant, pod weight (ton/acre), and 100-seed weight compared to when mineral fertilizers were used at different concentrations. The interaction of NPK nano-fertilizers with organic manure, along with NPK mineral fertilizers, increased protein levels with the increasing rate of NPK mineral fertilizers. Additionally, the interaction of NPK nano-fertilizers with organic manure increased proline content in seeds with the increasing rate of different mineral fertilizers. Overall, the application of NPK nano-fertilizers was found to improve soil fertility and increase crop productivity.